Development and validation of a new HPLC analytical method for the determination of diclofenac in tablets - Bushra Tuwfeeq Alquadeib (Elsevier, 2019)
A new selective and sensitive high-performance liquid chromatography (HPLC) method was developed for the quantification of diclofenac sodium (DS) in pharmaceutical dosage form using lidocaine as internal standard (IS). Chromatographic separation was achieved on a symmetry C18 column (4.6 mm × 150 mm, 3 μm spherical particles) using 0.05 M orthophosporic (pH 2.0) 35% and acetonitrile as 65%, as the mobile phase at a flow rate of 2.0 mL/min and monitored at 210 nm. The run time was 2 min.The method was validated to fulfill International Conference on Harmonisation (ICH) requirements and this validation included specificity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy, precision and robustness. The calibration curve was linear over the concentration range from 10 to 200 µg/ml, and lower limit of detection of 12.5 ng/ml. The accuracy and precision of the method were within the acceptable limit of ±20% at the lower limit of quantitation and ±15% at other concentrations. Diclofenac was unstable at room temperature it showed more than 25% loss after 24 h. While, DS is very stable at refrigerator 4 °C auto-sampler, freeze/thaw cycles and 30 days storage in a freezer at −35 ± 2 °C.All results were acceptable and this confirmed that the method is suitable for its intended use in routine quality control and assay of drugs. Keywords: Diclofenac, Reverse phase high performance liquid chromatography, HPLC